Studies of reduced graphene oxide (rGO)/CuS nanocomposite for supercapacitor applications - Singhal, R.; Thorne, D.; Chaudhary, M.; Kumar, A.; Bhardwaj, S.; Abazi, R.; Colon, A.; Gupta, R.K.; Scanley, J.; Broadbridge, C.C.; Singh, B.P.; LeMaire, P.K.; et al. (AIP Advances, 2023)
We have prepared CuS and CuS-rGO nanocomposites via the hydrothermal method. The physical properties of the synthesized materials were studied through x-ray diffraction and scanning electron microscopy. The supercapacitor characteristics were evaluated by cyclic voltammetric and galvanostatic charge–discharge studies. The cyclic voltammetric studies conform the pseudocapacitive nature of CuS and CuS-rGO electrodes. The specific capacitance of CuS was obtained as 207, 150, and 97 F/g at a current density of 0.5, 5, and 20 A/g, respectively. The rGO-CuS nanocomposite showed improved specific capacitance of 350, 251, and 149 F/g at current densities of 0.5, 5, and 20 A/g, respectively. © 2023 Author(s).
Keywords: dept.phy; peer-reviewed

Effect of reduce graphene oxide (Rgo) on electrochemical performance of Cus for supercapacitor applications - Singhal, Rahul; Thorne, David; Chaudhary, Manika; Bhardwaj, Shiva; Abazi, Rilind; Gupta, Ram K.; Scanley, Jules; Broadbridge, Christine C.; Singh, B. P.; LeMaire, Peter K.; Sharma, Rakesh K. (2023)
CuS and CuS-rGO nanocomposites were synthesized by the hydrothermal method. The synthesized CuS and rGO-CuS nanocomposite materials were physically characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM) and were evaluated electrochemically for supercapacitor applications. The specific capacitance of CuS was determined to be 207 F/g, 150 F/g, and 97 F/g at a current density of 0.5 A/g, 5 A/g, and 20 A/g, respectively. The rGO-CuS nanocomposite showed improved specific capacitance of 350 F/g, 251 F/g, and 149 F/g at a current density of 0.5 A/g, 5 A/g, and 20 A/g, respectively.
Keywords: CuS; SEM; Supercapacitors; dept.phy; rGO; specific capacitance

A New Stellar Companion to GJ 835 - Clark, Catherine A.; Horch, Elliott; Davidson, James W. (Research notes of the AAS, 2023)
Keywords: dept.phy

Nanotechnology in Electronics, Photonics, Biosensors and Energy Systems - Jain, F.; Braodbridge, C.; Gherasimova, M.; Hong, X. Tang (2023)
Keywords: dept.phy

Experimental Status of the Chiral Magnetic Effect - Finch, Evan (EDP Sciences, 2023)
Keywords: dept.phy

Erratum to: Evidence of mass ordering of charm and bottom quark energy loss in Au+Au collisions at RHIC - STAR Collaboration (The European Physical Journal C, 2023)
Keywords: dept.phy; peer-reviewed

Interactions between two adjacent convection rolls in turbulent Rayleigh-Bénard convection - Brown, Eric; Ji, Dandan (Physical Review Fluids, 2023)
We seek to develop a low-dimensional model for the interactions between horizontally adjacent turbulent convection rolls. This was tested in Rayleigh-Bénard convection experiments with two adjacent cubic cells with a partial wall in between. Observed stable states include both counterrotating and corotating states for Rayleigh number 7.6×107< Ra <3.5×109 and Prandtl number 6.41. The stability of each of these states and their dynamics can be modeled low-dimensionally by stochastic ordinary differential equations of motion in terms of the orientation, amplitude, and mean temperature of each convection roll. The form of the interaction terms is predicted based on an effective turbulent diffusion of temperature between the adjacent rolls, which is projected onto the neighboring rolls with sinusoidal temperature profiles. With measurements of a constant coefficient for effective thermal turbulent diffusion, quantitative predictions are made for the nine forcing terms which affect stable fixed points of the corotating and counterrotating states for 5.5×108< Ra <3.5×109. Predictions are found to be accurate within a factor of 3 of experiments. This suggests that the same turbulent thermal diffusivity that describes macroscopically averaged heat transport also controls the interactions between neighboring convection rolls. The surprising stability of corotating states is due to the temperature difference between the neighboring rolls becoming large enough that the heat flux between the rolls stabilizes the temperature profile of aligned corotating states. This temperature difference can be driven with an asymmetry, for example, by heating the plates of the two cells to different mean temperatures. When such an asymmetry is introduced, it also shifts the orientations of the rolls of counterrotating states in opposite directions away from their preferred orientation, which is otherwise due to the geometry of the cell. As the temperature difference between the plates of the different cells is increased, the shift in orientation increases until the counterrotating states become unstable and only corotating states are stable. At very large temperature differences between cells, both the counterrotating and predicted corotating states become unstable; instead we observe a corotating state with much larger temperature difference between the rolls that cannot be explained by turbulent thermal diffusion. Spontaneous switching between corotating and counterrotating states is also observed, including in nominally symmetric systems. Switching to counterrotating states occurs mainly due to cessation (a significant weakening of a convection roll), which reduces damping on changes in orientation, allowing the orientation to change rapidly due to diffusive fluctuations. Switching to corotating states is mainly driven by smaller diffusive fluctuations in the orientation, amplitude, and mean temperature of rolls, which have a positive feedback that destabilizes the counterrotating state. © 2023 American Physical Society.
Keywords: dept.phy; peer-reviewed

Measurements of the Elliptic and Triangular Azimuthal Anisotropies in Central He 3 +Au, d+Au and p+Au Collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2023)
The elliptic (v2) and triangular (v3) azimuthal anisotropy coefficients in central He3+Au, d+Au, and p+Au collisions at sNN=200 GeV are measured as a function of transverse momentum (pT) at midrapidity (|η|<0.9), via the azimuthal angular correlation between two particles both at |η|<0.9. While the v2(pT) values depend on the colliding systems, the v3(pT) values are system independent within the uncertainties, suggesting an influence on eccentricity from subnucleonic fluctuations in these small-sized systems. These results also provide stringent constraints for the hydrodynamic modeling of these systems. © 2023 American Physical Society.
Keywords: dept.phy; peer-reviewed

Measurement of electrons from open heavy-flavor hadron decays in Au+Au collisions at √sNN = 200 GeV with the STAR detector - STAR Collaboration (Journal of High Energy Physics, 2023)
We report a new measurement of the production of electrons from open heavy-flavor hadron decays (HFEs) at mid-rapidity (|y| < 0.7) in Au+Au collisions at sNN = 200 GeV. Invariant yields of HFEs are measured for the transverse momentum range of 3.5 < p T < 9 GeV/c in various configurations of the collision geometry. The HFE yields in head-on Au+Au collisions are suppressed by approximately a factor of 2 compared to that in p + p collisions scaled by the average number of binary collisions, indicating strong interactions between heavy quarks and the hot and dense medium created in heavy-ion collisions. Comparison of these results with models provides additional tests of theoretical calculations of heavy quark energy loss in the quark-gluon plasma. [Figure not available: see fulltext.] © 2023, The Author(s).
Keywords: Heavy Ion Experiments; Heavy Quark Production; Heavy-Ion Collision; dept.phy; peer-reviewed

Star-image Centering with Deep Learning: HST/WFPC2 Images - Casetti-Dinescu, Dana I.; Girard, Terrence M.; Baena-Gallé, Roberto; Martone, Max; Schwendemann, Kate (Publications of the Astronomical Society of the Pacific, 2023)
A deep learning (DL) algorithm is built and tested for its ability to determine centers of star images in HST/WFPC2 exposures, in filters F555W and F814W. These archival observations hold great potential for proper-motion studies, but the undersampling in the camera’s detectors presents challenges for conventional centering algorithms. Two exquisite data sets of over 600 exposures of the cluster NGC 104 in these filters are used as a testbed for training and evaluating the DL code. Results indicate a single-measurement standard error from 8.5 to 11 mpix, depending on the detector and filter. This compares favorably to the ∼20 mpix achieved with the customary “effective point spread function (PSF)” centering procedure for WFPC2 images. Importantly, the pixel-phase error is largely eliminated when using the DL method. The current tests are limited to the central portion of each detector; in future studies, the DL code will be modified to allow for the known variation of the PSF across the detectors.
Keywords: dept.phy

TFAW survey II: Six newly validated planets and 13 planet candidates from K2 - Del Ser, D.; Fors, O.; Del Alcázar, M.; Dyachenko, V.; Horch, E.P.; Tokovinin, A.; Ziegler, C.; Van Belle, G.T.; Clark, C.A.; Hartman, Z.D. (Monthly Notices of the Royal Astronomical Society, 2023)
Searching for Earth-sized planets in data from Kepler's extended mission (K2) is a niche that still remains to be fully exploited. The TFAW survey is an ongoing project that aims to re-analyse all light curves in K2 C1-C8 and C12-C18 campaigns with a wavelet-based detrending and denoising method, and the period search algorithm TLS to search for new transit candidates not detected in previous works. We have analysed a first subset of 24 candidate planetary systems around relatively faint host stars (10.9 < Kp < 15.4) to allow for follow-up speckle imaging observations. Using vespa and TRICERATOPS, we statistically validate six candidates orbiting four unique host stars by obtaining false-positive probabilities smaller than 1 per cent with both methods. We also present 13 vetted planet candidates that might benefit from other, more precise follow-up observations. All of these planets are sub-Neptune-sized with two validated planets and three candidates with sub-Earth sizes, and have orbital periods between 0.81 and 23.98 d. Some interesting systems include two ultra-short-period planets, three multiplanetary systems, three sub-Neptunes that appear to be within the small planet Radius Gap, and two validated and one candidate sub-Earths (EPIC 210706310.01, K2-411 b, and K2-413 b) orbiting metal-poor stars. © 2022 The Author(s) Published by Oxford University Press on behalf of Royal Astronomical Society.
Keywords: dept.phy; instrumentation: high angular resolution; methods: data analysis; peer-reviewed; planets and satellites: general; planets and satellites: terrestrial planets; techniques: photometric

A handheld visible resonance raman analyzer used in intraoperative detection of human glioma - Zhang, Liang; Zhou, Yan; Wu, Binlin; Zhang, Shengjia; Zhu, Ke; Liu, Cheng-Hui; Yu, Xinguang; Alfano, Robert R. (Cancers, 2023)
There is still a lack of reliable intraoperative tools for glioma diagnosis and to guide the maximal safe resection of glioma. We report continuing work on the optical biopsy method to detect glioma grades and assess glioma boundaries intraoperatively using the VRR-LRRTM Raman analyzer, which is based on the visible resonance Raman spectroscopy (VRR) technique. A total of 2220 VRR spectra were collected during surgeries from 63 unprocessed fresh glioma tissues using the VRR-LRRTM Raman analyzer. After the VRR spectral analysis, we found differences in the native molecules in the fingerprint region and in the high-wavenumber region, and differences between normal (control) and different grades of glioma tissues. A principal component analysis–support vector machine (PCA-SVM) machine learning method was used to distinguish glioma tissues from normal tissues and different glioma grades. The accuracy in identifying glioma from normal tissue was over 80%, compared with the gold standard of histopathology reports of glioma. The VRR-LRRTM Raman analyzer may be a new label-free, real-time optical molecular pathology tool aiding in the intraoperative detection of glioma and identification of tumor boundaries, thus helping to guide maximal safe glioma removal and adjacent healthy tissue preservation.
Keywords: dept.phy; glioma; human brain; intraoperative; optical biopsy; optical molecular pathology; peer-reviewed; portable optical-fiber-probe Raman analyzer; visible resonance Raman (VRR)

Azimuthal anisotropy measurement of (multi)strange hadrons in Au+Au collisions at sNN =54.4 GeV - STAR Collaboration (Physical Review C, 2023)
Azimuthal anisotropy of produced particles is one of the most important observables used to access the collective properties of the expanding medium created in relativistic heavy-ion collisions. In this paper, we present second (v2) and third (v3) order azimuthal anisotropies of KS0, φ, Λ, Ξ, and ω at midrapidity (|y|<1) in Au+Au collisions at sNN=54.4 GeV measured by the STAR detector. The v2 and v3 are measured as a function of transverse momentum and centrality. Their energy dependence is also studied. v3 is found to be more sensitive to the change in the center-of-mass energy than v2. Scaling by constituent quark number is found to hold for v2 within 10%. This observation could be evidence for the development of partonic collectivity in 54.4 GeV Au+Au collisions. Differences in v2 and v3 between baryons and antibaryons are presented, and ratios of v3/v23/2 are studied and motivated by hydrodynamical calculations. The ratio of v2 of φ mesons to that of antiprotons [v2(φ)/v2(p¯)] shows centrality dependence at low transverse momentum, presumably resulting from the larger effects from hadronic interactions on antiproton v2. © 2023 American Physical Society.
Keywords: dept.phy; peer-reviewed

Pion, kaon, and (anti)proton production in U+U collisions at sNN =193 GeV measured with the STAR detector - STAR Collaboration (Physical Review C, 2023)
We present the first measurements of transverse momentum spectra of π±, K±, p(p¯) at midrapidity (|y|<0.1) in U+U collisions at sNN= 193 GeV with the STAR detector at the Relativistic Heavy Ion Collider (RHIC). The centrality dependence of particle yields, average transverse momenta, particle ratios and kinetic freeze-out parameters are discussed. The results are compared with the published results from Au+Au collisions at sNN= 200 GeV in STAR. The results are also compared to those from A Multi-Phase Transport (ampt) model. © 2023 American Physical Society.
Keywords: dept.phy; peer-reviewed

Beam energy dependence of fifth- and sixth-order net-proton number fluctuations in Au+Au collisions at RHIC - STAR Collaboration (Physical Review Letters, 2023)
We report the beam energy and collision centrality dependence of fifth and sixth order cumulants (C5, C6) and factorial cumulants (κ5, κ6) of net-proton and proton number distributions, from center-of-mass energy (sNN) 3 GeV to 200 GeV Au+Au collisions at RHIC. Cumulant ratios of net-proton (taken as proxy for net-baryon) distributions generally follow the hierarchy expected from QCD thermodynamics, except for the case of collisions at 3 GeV. The measured values of C6/C2 for 0%-40% centrality collisions show progressively negative trend with decreasing energy, while it is positive for the lowest energy studied. These observed negative signs are consistent with QCD calculations (for baryon chemical potential, μB≤110 MeV) which contains the crossover transition range. In addition, for energies above 7.7 GeV, the measured proton κn, within uncertainties, does not support the two-component (Poisson+binomial) shape of proton number distributions that would be expected from a first-order phase transition. Taken in combination, the hyperorder proton number fluctuations suggest that the structure of QCD matter at high baryon density, μB∼750 MeV at sNN=3 GeV is starkly different from those at vanishing μB∼24 MeV at sNN=200 GeV and higher collision energies. © 2023 American Physical Society.
Keywords: dept.phy; peer-reviewed

Search for the chiral magnetic effect in Au+Au collisions at sNN=27 GeV with the STAR forward event plane detectors - STAR Collaboration (Physics Letters B, 2023)
A decisive experimental test of the Chiral Magnetic Effect (CME) is considered one of the major scientific goals at the Relativistic Heavy-Ion Collider (RHIC) towards understanding the nontrivial topological fluctuations of the Quantum Chromodynamics vacuum. In heavy-ion collisions, the CME is expected to result in a charge separation phenomenon across the reaction plane, whose strength could be strongly energy dependent. The previous CME searches have been focused on top RHIC energy collisions. In this Letter, we present a low energy search for the CME in Au+Au collisions at sNN=27 GeV. We measure elliptic flow scaled charge-dependent correlators relative to the event planes that are defined at both mid-rapidity |η|<1.0 and at forward rapidity 2.1<|η|<5.1. We compare the results based on the directed flow plane (Ψ1) at forward rapidity and the elliptic flow plane (Ψ2) at both central and forward rapidity. The CME scenario is expected to result in a larger correlation relative to Ψ1 than to Ψ2, while a flow driven background scenario would lead to a consistent result for both event planes. In 10-50% centrality, results using three different event planes are found to be consistent within experimental uncertainties, suggesting a flow driven background scenario dominating the measurement. We obtain an upper limit on the deviation from a flow driven background scenario at the 95% confidence level. This work opens up a possible road map towards future CME search with the high statistics data from the RHIC Beam Energy Scan Phase-II.
Keywords: Beam energy scan; Chiral magnetic effect; Heavy-ion collisions; dept.phy; peer-reviewed

Beam energy dependence of the linear and mode-coupled flow harmonics in Au+Au collisions - STAR Collaboration (Physics Letters B, 2023)
The linear and mode-coupled contributions to higher-order anisotropic flow are presented for Au+Au collisions at sNN = 27, 39, 54.4, and 200 GeV and compared to similar measurements for Pb+Pb collisions at the Large Hadron Collider (LHC). The coefficients and the flow harmonics' correlations, which characterize the linear and mode-coupled response to the lower-order anisotropies, indicate a beam energy dependence consistent with an influence from the specific shear viscosity (η/s). In contrast, the dimensionless coefficients, mode-coupled response coefficients, and normalized symmetric cumulants are approximately beam-energy independent, consistent with a significant role from initial-state effects. These measurements could provide unique supplemental constraints to (i) distinguish between different initial-state models and (ii) delineate the temperature (T) and baryon chemical potential (μB) dependence of the specific shear viscosity ηs(T,μB).
Keywords: Collectivity; Correlation; Shear viscosity; dept.phy; peer-reviewed

Stokes shift spectroscopy and machine learning for label-free human prostate cancer detection - Pu, Y.; Wu, B.; Mo, H.; Alfano, R.R. (Optics Letters, 2023)
The Stokes shift spectra (S3) of human cancerous and normal prostate tissues were collected label free at a selected wavelength interval of 40 nm to investigate the efficacy of the approach based on three key molecules—tryptophan, collagen, and reduced nicotinamide adenine dinucleotide (NADH)—as cancer biomarkers. S3 combines both fluorescence and absorption spectra in one scan. The S3 spectra were analyzed using machine learning (ML) algorithms, including principal component analysis (PCA), nonnegative matrix factorization (NMF), and support vector machines (SVMs). The components retrieved from the S3 spectra were considered principal biomarkers. The differences in the weights of the components between the two types of tissues were found to be significant. Sensitivity, specificity, and accuracy were calculated to evaluate the performance of SVM classification. This research demonstrates that S3 spectroscopy is effective for detecting the changes in the relative concentrations of the endogenous fluorophores in tissues due to the development of cancer label free. © 2023 Optica Publishing Group.
Keywords: dept.phy; peer-reviewed

Pattern of global spin alignment of ϕ and K*0 mesons in heavy-ion collisions - STAR Collaboration (Nature, 2023)
Notwithstanding decades of progress since Yukawa first developed a description of the force between nucleons in terms of meson exchange1, a full understanding of the strong interaction remains a considerable challenge in modern science. One remaining difficulty arises from the non-perturbative nature of the strong force, which leads to the phenomenon of quark confinement at distances on the order of the size of the proton. Here we show that, in relativistic heavy-ion collisions, in which quarks and gluons are set free over an extended volume, two species of produced vector (spin-1) mesons, namely ϕ and K*0, emerge with a surprising pattern of global spin alignment. In particular, the global spin alignment for ϕ is unexpectedly large, whereas that for K*0 is consistent with zero. The observed spin-alignment pattern and magnitude for ϕ cannot be explained by conventional mechanisms, whereas a model with a connection to strong force fields2–6, that is, an effective proxy description within the standard model and quantum chromodynamics, accommodates the current data. This connection, if fully established, will open a potential new avenue for studying the behaviour of strong force fields. © 2023, The Author(s), under exclusive licence to Springer Nature Limited.
Keywords: dept.phy; peer-reviewed